Implementasi Fungsi Pengawasan DPRD Kabupaten Tabanan Terhadap Pelaksanaan Perda Nomor 14 Tahun 2018 Tentang Penataan Toko Swalayan - Ayu Putu Putri Shinta Dewi; I Gusti Bagus Suryawan; Ni Luh Putu Suryani (Jurnal Analogi Hukum, 2019)
Abstract Representative Council (DPRD) is an element of regional government administering that is equal to the local government in making regional regulations in implementing regional autonomy, so that a good performance is needed between the executive and the legislative to create good governance. This study examines the mechanism of the implementation of the supervisory function, the follow-up to violations of a Regional Regulation, obstacles and efforts to overcome the obstacles that arise in carrying out the supervisory function carried out by the Tabanan Regency DPRD on the implementation of Regional Regulations. Approach to the problem used in empirical legal research is the legal sociology approach where legal research is taken from the facts in a society, legal entities or government, observation and documentation. The results of this study indicate that the implementation of the supervisory function of DPRD Tabanan Regency on the implementation of local regulations has been carried out properly in accordance with applicable regulations and mechanisms, and supervision of these regulations is carried out with the following mechanism: DPRD Conducts work meetings, field visits, hearings. The follow-up action of DPRD Tabanan Regency on violations in Regional Regulation number 14 in 2018 concerning the Arrangement of Supermarkets is by sending recommendations to the relevant OPD to provide shopkeepers with a warning letter that violates the provisions and if it is not heeded the shop must be closed. The obstacles that are often faced are the lack of understanding among council members about the limitations and scope of conducting supervision of the Perda and the lack of participation from the community. The step of the Tabanan Regency DPRD to overcome obstacles is by providing experts in order to support the smooth functioning of the DPRD in carrying out the oversight function. Keywords: Local Regulation ; Representative Council Tabanan Regency; Supervision Function Abstrak Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Tabanan merupakan unsur penyelenggaran pemerintahan daerah yang sejajar dengan pemrintah daerah dalam membuat peraturan daerah dalam melaksanakan otonomi daerah, sehingga diperlukan sebuah kinerja yang baik antara eksekutif dan legislatif untuk menciptakan pemerintahan yang baik. Penelitian ini mengkaji mengenai mekanisme pelaksanaan fungsi pengawasan, upaya hukum terhadap pelanggaran sebuah Perda, hambatan-hmbatan serta upaya mengatasi hambatan-hambatan yang timbul dalam melakukan fungsi pengawasan yang dilakukan oleh DPRD Kabupaten Tabanan terhada pelaksanaan Peraturan Daerah. Pendekatan masalah yang dipergunakan dalam penelitian hukum empiris ini yaitu pendekatan sosiologi. Hasil penelitian ini menunjukkan bahwa pelaksanaan fungsi pengawasan DPRD Kabupaten Tabanan terhadap Perda dilakukan dengan mekanisme sebagai berikut: DPRD Melakukan rapat kerja, kunjungan lapangan, rapat dengar pendapat. Tindak lanjut DPRD Kabupaten Tabanan terhadap pelanggaran dalam Perda Nomor 14 Tahun 2018 tentang Penataan Toko Swalayan adalah dengan cara mengirimkan rekomendasi kepada OPD terkait untuk memberikan surat peringatan terlebih dahulu kepada pemilik toko yang melanggar ketentuan dan apabila tidak diindahkan maka toko tersebut wajib untuk ditutup. Sedangkanyang menjadi hambatan DPRD dalam melakukan fungsi pengawasan adalah kurangnya pemahaman anggota dewan terhadap ruang lingkup dan batasan-batasan dalam melakukan fungsi pengawasan dan kurangnya pasrtisipasi dari masyarakat. Langkah DPRD Kabupaten Tabanan dalam mengatasi hambatan adalah dengan cara menyediakan tenaga ahli khusus dalam rangka mendukung kelancaran DPRD dalam melaksanakan fungsi pengawasan. Kata Kunci: Perda; DPRD Kabupaten Tabanan; fungsi Pengawasan